Evaluation of the activities of a wrestling coach - Sobyanin, F.I.; Makashev, Sh.A.; Kondratenko, P.P. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to develop a methodology for evaluating the activities of a wrestling coach. Methods and structure of the study. Scientific work is organized at the faculties of physical culture at the University of Innovation and Technology of Western Kazakhstan, Utemisov Western Kazakhstan University and Belgorod State National Research University in 2017-2021. The analysis of special scientific literature, a survey of coaches and athletes, the study of competition protocols and regulatory documents, analysis of performance results, and mathematical modeling were used as research methods. Results and conclusions. The proposed methodology is based on the well-known and specific indicators of professional achievements of an individual coach and the received sports achievements of each athlete trained by him, entered into the formula for mathematical calculations. The meaning of these calculations is to determine the arithmetic mean from the sum of the achievements of the coach and his athletes, divided by the number of athletes with the coach. The developed methodology for determining the effectiveness of the activity of a coach in freestyle wrestling and wrestling Kazakhsha-kures is a set of evaluative actions of the coach and his students, followed by the introduction of indicators into the proposed formula and the calculation of the coefficient of effectiveness of the coach. The technique is universal, practical, can be easily modified, and is widely used not only in martial arts, but also in other sports. It allows you to systematically monitor the dynamics of the effectiveness of the work of coaches and compare the effectiveness of both individual coaches and their groups within the same sports organization or between them.